Additional Costs of Polymyalgia Rheumatica With Giant Cell Arteritis. Issue 8 (11th July 2019) - Mounié, Michael; Pugnet, Grégory; Savy, Nicolas; Lapeyre‐Mestre, Maryse; Molinier, Laurent; Costa, Nadège
Abstract : Objective: To assess and compare direct costs between patients with giant cell arteritis (GCA) that is associated or not associated with polymyalgia rheumatic (PMR), and to identify the additional cost drivers due to PMR. Methods: A population‐based, retrospective cohort study using the French National Health Insurance System Database was conducted. Cost analysis was performed from the French health insurance perspective and direct medical and nonmedical costs were taken into account (based on 2014 costs [€]). Costs were analyzed according to different components and divided into 6‐month periods to assess care consumption. Longitudinal multivariate analyses, using generalized estimating equations, were used to adjust the effect of PMR on the mean cost over time. Results: Analyses were performed on 100 incident patients with GCA, 54 of whom had PMR. The cumulative additional cost due to PMR was €8, 801 for 3 years, and €10, 532 for 5 years. The significant additional costs occurred especially during the second and third years of follow‐up, amounting to €1, 769 between 12 and 18 months ( P = 0.02), €1, 924 between 18 and 24 months ( P = 0.17), €1, 458 between 24 and 30 months ( P = 0.08), and €1, 307 between 30 and 36 months ( P = 0.07). The most important cost drivers were inpatient stays, paramedic procedures, and medications. Multivariate analyses showed a significant effect of PMR on mean cost during the first 3 years of follow‐up (relative risk 1.76 [95% confidence interval 1.03–2.99], P = 0.038). Conclusion: To our knowledge, this study is the first to accurately assess the cost of PMR care in patients with GCA and to highlight that PMR is largely responsible for the high cost of GCA.